The Determinants of Home-Based Worker: Evidence From Married Women in Indonesia - Yefin Amandri Meidika; Lilik Sugiharti; Neny Aditina; Ary Fauziah Amini (MediaTrend, 2019)
A home-based worker is defined as a worker who performs to work at home or a neighbor's home. Using data from the National Labor Force Survey (Sakernas 2018), this research aims to analyze the determinants of married women becoming home-based workers. We build two models using internet access to categorize a dependent variable. Observation unit in this research is employed married women aged 15 years and over. The models in this research are estimated by multinomial logit. Independent variables that examined including socio-demographic characteristics, family characteristics, work characteristics, and regional characteristics. Our finding shows that younger women, having children under age 5, having employed household head, working on industry sector as sales and service worker, self-employed and had work training experience are more likely to be a home-based worker in both models.